2022
DOI: 10.1002/aenm.202202175
|View full text |Cite
|
Sign up to set email alerts
|

Building Efficient and Durable Hetero‐Interfaces on a Perovskite‐Based Electrode for Electrochemical CO2 Reduction

Abstract: Solid oxide electrochemical cells (SOECs) have demonstrated the potential to be highly efficient devices for electrochemical CO2 reduction (CO2R) at intermediate temperatures. However, the performance and widespread applications for CO2R largely hinge on the sluggish reaction kinetics and poor durability of the state‐of‐the‐art electrodes. Here, the findings in enhancing the reaction activity and durability of a perovskite‐based electrode are reported, Sr2Fe1.5Mo0.3Cu0.2O6‐δ (SF1.5MC), for electrochemical oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 85 publications
0
47
1
Order By: Relevance
“…Regulation of the p O2 is achieved by adjusting the ratio of pure oxygen to nitrogen and controlling the total flow rate to 100 ml min −1 . Besides, we applied MATLAB R2018b to perform the DRT analysis, and the regularization parameter was chosen to be 10 −3 52–55 . When the p O2 gradually decreases, the R p rises noticeably.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of the p O2 is achieved by adjusting the ratio of pure oxygen to nitrogen and controlling the total flow rate to 100 ml min −1 . Besides, we applied MATLAB R2018b to perform the DRT analysis, and the regularization parameter was chosen to be 10 −3 52–55 . When the p O2 gradually decreases, the R p rises noticeably.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we applied MATLAB R2018b to perform the DRT analysis, and the regularization parameter was chosen to be 10 −3 . [52][53][54][55] When the p O2 gradually decreases, the R p rises noticeably. For example, as shown in Figure 3A, when the p O2 increased from 0.1 to 0.8, the R p of PBCC decreased from 0.139 to 0.061 Ω cm 2 , which is consistent with the fact that increased oxygen concentration can promote the ORR reaction.…”
Section: Performance Of Symmetrical Cellmentioning
confidence: 98%
“…As shown in Figure b (bottom) and Figure S8b (bottom), FeCoNiCuAl-SDC anode testing under CH 4 fuel gas also exhibits a lower polarization impedance, which corresponds to the higher power density (Figure c). We employed the DRT to assess the EIS data, which was used to conduct additional research on the influence of temperature and gas partial pressure for the electrochemical reaction of the FeCoNiCuX-SDC anodes. , Each DRT curve exhibits three distinct peaks in the low-, intermediate-, and high-frequency region, which correspond to gas adsorption and dissociation, ion surface exchange, and bulk diffusion, charge transfer process. The decrease in the characteristic frequency may signify the loss of electrode reaction kinetics . As shown in Figures c,d and S3c,d, under H 2 and CH 4 atmospheres, it was found that the change of temperature mainly affected the low-frequency region (then the intermediate-frequency region).…”
Section: Resultsmentioning
confidence: 99%
“…The Sr 2 Fe 1.2 Mg 0.2 Mo 0.6 O 6−δ material shows much higher conductivity in air and comparable values in the reducing condition with Sr 2 FeMo 2/3 Mg 1/3 O 6−δ oxide (4–5 S·cm −1 in air, and 9–13 S·cm −1 in H 2 at 600–800 °C) [ 38 ]. In addition, the measured electrical conductivity of Sr 2 Fe 1.2 Mg 0.2 Mo 0.6 O 6−δ is much higher than the σ value of Sr 2 MgMoO 6−δ [ 49 ], Sr 2 Fe 1.5 Mo 0.3 Cu 0.2 O 6−δ [ 35 ], Sr 2−x Ba x MgMoO 6−δ , and Sr 2−x Ba x MnMoO 6−δ [ 24 , 25 ]. In addition, the chemical diffusion coefficient D and surface exchange constant k of Sr 2 Fe 1.2 Mg 0.2 Mo 0.6 O 6−δ have been determined by the mass relaxation technique ( Figure 6 b,c).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, SOFC cells with (PrBa) 0.95 (Fe 0.9 Mo 0.1 ) 2 O 5+δ anodes also show outstanding performance in H 2 S-containing fuel (1.18 Wcm −2 @800 °C in H 2 +100ppmH 2 S), which indicates this material also has excellent tolerance to sulfur poisoning [ 18 ]. The copper-doped Sr 2 Fe 1.5 Mo 0.3 Cu 0.2 O 6−δ oxide with enhanced reaction activity and durability was studied for the electrochemical oxidation of H 2 and reduction of CO 2 , showing a peak SOFC power output of 1.51 W cm −2 in hydrogen and a current density of 1.94 A cm −2 at 1.4 V in the reduction of CO 2 to CO [ 35 ]. Ti-doped Sr 2 Fe 1.4−x Ti x Mo 0.6 O 6−δ double perovskites with an improved structural stability ascribed to the strong Ti-O bond were studied as novel anode materials for SOFCs, with Sr 2 Fe 1.3 Ti 0.1 Mo 0.6 O 6−δ anode-based cells delivering a very good power density exceeding 0.64 W cm2 at 900 °C in humidified H 2 [ 36 ].…”
Section: Introductionmentioning
confidence: 99%